Photosynthesis and Carbon Partitioning in Transgenic Tobacco Plants Deficient in Leaf Cytosolic Pyruvate Kinase - Grodzinski, Bernard (American Society of Plant Physiologists, 1999)
Whole-plant diurnal C exchange analysis provided a noninvasive estimation of daily net C gain in transgenic tobacco (Nicotiana tabacum L.) plants deficient in leaf cytosolic pyruvate kinase (PK(c)−). PK(c)− plants cultivated under a low light intensity (100 μmol m(−2) s(−1)) were previously shown to exhibit markedly reduced root growth, as well as delayed shoot and flower development when compared with plants having wild-type levels of PK(c) (PK(c)+). PK(c)− and PK(c)+ source leaves showed a similar net C gain, photosynthesis over a range of light intensities, and a capacity to export newly fixed (14)CO(2) during photosynthesis. However, during growth under low light the nighttime, export of previously fixed (14)CO(2) by fully expanded PK(c)− leaves was 40% lower, whereas concurrent respiratory (14)CO(2) evolution was 40% higher than that of PK(c)+ leaves. This provides a rationale for the reduced root growth of the PK(c)− plants grown at low irradiance. Leaf photosynthetic and export characteristics in PK(c)− and PK(c)+ plants raised in a greenhouse during winter months resembled those of plants grown in chambers at low irradiance. The data suggest that PK(c) in source leaves has a critical role in regulating nighttime respiration particularly when the available pool of photoassimilates for export and leaf respiratory processes are low.